The right of consumers to reject goods under the Consumer Protection Act 1999 – real or illusory? - Amin, Naemah (2009)
As the main statute on consumer protection in Malaysia, the Consumer Protection Act 1999 deals with various aspects of consumer protection including a supply of goods. The CPA not only provides a new set of guarantees which are implied in every contract of supply of goods to consumers but also introduces a different remedial scheme in cases of breach of the guarantees. In addition to repair or replacement of defective goods, consumers who are not satisfied with the goods for certain valid reasons may exercise the right to reject the goods. The paper aims to analyse relevant provisions of the CPA relating to this right which include the grounds for rejection, procedure of rejection and limitations in enforcing the right. It ultimately answers the question as to whether the right to reject goods is really practical and favourable to the consumer or it is just exist on paper.